2009
DOI: 10.1248/bpb.32.1392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bupleurum falcatum</i> on the Stress-Induced Impairment of Spatial Working Memory in Rats

Abstract: Many studies have shown that Bupleurum falcatum (BF), which is widely used in the treatment of various psychosomatic diseases in traditional Oriental medicine, is an effective therapeutic intervention for memory impairment. The purpose of this study was to examine the effect of BF on stress-induced alterations in learning and memory in rats using the Morris water maze (MWM) and elevated plus maze (EPM) behavioral tests. In addition, we examined the effects of BF treatment on the cholinergic system, as indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Concanavalin A or phorbol esterstimulated T cell activation was inhibited by SD through reducing the phosphorylation of IκB and JNK (Leung et al, 2005). In addition, BFE treatment effectively reversed immobilization stressinduced impairment of spatial working memory in rats (Lee et al, 2009), and acute spinal cord injuryinduced decreases in locomotor activity by inhibiting the expression of matrix metalloproteinases (Lee et al, 2010). These reports suggest that BFE and its active components may penetrate the blood brain barrier in vivo and exert anti-inflammatory effects in the central nervous system.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Concanavalin A or phorbol esterstimulated T cell activation was inhibited by SD through reducing the phosphorylation of IκB and JNK (Leung et al, 2005). In addition, BFE treatment effectively reversed immobilization stressinduced impairment of spatial working memory in rats (Lee et al, 2009), and acute spinal cord injuryinduced decreases in locomotor activity by inhibiting the expression of matrix metalloproteinases (Lee et al, 2010). These reports suggest that BFE and its active components may penetrate the blood brain barrier in vivo and exert anti-inflammatory effects in the central nervous system.…”
Section: Discussionmentioning
confidence: 78%
“…Among these, saikosaponins have been reported as the major biologically active components (Liau et al, 2007) and possess various pharmacological activities, including anti-hepatitis, anti-hepatoma, anti-inflammatory, antibacterial, and immune-modulating effects (Cheng et al, 2006;Guo et al, 2000). Treatment with ethanol extract of BF (BFE) improved behavioral defects after spinal cord injury by inhibiting activation of matrix metalloproteinase-2 and -9, resulting in reduced inflammation (Lee et al, 2010) and decreased stress-induced memory impairment (Lee et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that repeated IMO stress in the rats slowed the escape latency in the MWM test, demonstrating deficits in spatial learning ability and reference memory (Kim et al 2007). The escape latency score in the spatial probe tests of the MWM test is considered to reflect long-term spatial memory ability (Lee et al 2009). This indicates that administration of AgMx ameliorated long-term memory deficits significantly in rats following repeated IMO stress-induced dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the pharmacological effects of B. falcatum on the central nervous system through modulation of the HPA axis. B. falcatum has a protective effect against repeated immobilization stress induced neuronal and cognitive impairments, and they suggest that B. falcatum may be useful in the treatment of stress induced memory impairment [109].…”
Section: Miscellaneous Tkm Plantsmentioning
confidence: 99%